2018
DOI: 10.1128/aac.00512-18
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Substrate Characterization of 22 Antituberculosis Drugs for Multiple Solute Carrier (SLC) Uptake Transporters In Vitro

Abstract: The substrate potentials of antituberculosis drugs on solute carrier (SLC) transporters are not well characterized to date, despite a well-established understanding of their drug dispositions and pharmacokinetics. In this study, we investigated comprehensively the substrate potentials of the 22 currently available antituberculosis drugs for SLC family transporter-mediated uptake, using oocytes and stably transfected HEK-293 cells The result suggested that ethambutol, isoniazid, amoxicillin, and prothionamide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…To this end, PK data obtained in critically ill children of different ages after the concomitant administration of clavulanic acid and amoxicillin was used. Each drug was assumed a probe for their specific elimination pathway, i.e., clavulanic acid for glomerular filtration (GF) and amoxicillin for a combination of GF and ATS through OAT1,3 ( 13 , 14 ). With this methodology the ontogeny function of OAT1,3 could be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, PK data obtained in critically ill children of different ages after the concomitant administration of clavulanic acid and amoxicillin was used. Each drug was assumed a probe for their specific elimination pathway, i.e., clavulanic acid for glomerular filtration (GF) and amoxicillin for a combination of GF and ATS through OAT1,3 ( 13 , 14 ). With this methodology the ontogeny function of OAT1,3 could be estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Moxifloxacin, which was characterized as a potent inhibitor of OCT1, could significantly inhibit the cellular transport of EMB ( Te Brake et al, 2016 ). Later, Parvez et al confirmed that EMB, amoxicillin, INH and prothionamide were novel substrates of OCT1 and as expected, the OCT1 inhibitor verapamil could strongly reduce their cellular uptake ( Parvez et al, 2018 ). In addition, they found that the DDI indices of OCT1-mediated uptake of EMB and prothionamide were similar to that of verapamil, suggesting a strong in vivo potential of DDIs for these drugs with others.…”
Section: Interaction Of Organic Cation Transporter 1 With Clinical mentioning
confidence: 76%
“…Isoniazid has been reported to be a substrate of three solute carrier (SLC) transporters i.e. OCT2, OAT1, and OAT3 (35). These three SLC transporters are expressed in several tissues including brain and the blood-brain-barrier, and typically facilitate uptake of drug substrates (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, isoniazid showed a good distribution of drug over the blood-brain barrier, with median CSF-to-plasma ratios of 1.44 for fast acetylators and 1.48 for slow acetylators, resulting in a higher concentration in CSF than in plasma. Isoniazid has been reported to be a substrate of three solute carrier (SLC) transporters, i.e., OCT2, OAT1, and OAT3 ( 34 ). These three SLC transporters are expressed in several tissues, including brain tissue and the blood-brain barrier, and typically facilitate uptake of drug substrates (i.e., influx) into the central nervous system ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%